2020
DOI: 10.1037/pha0000347
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral economic measurement of cigarette demand: A descriptive review of published approaches to the cigarette purchase task.

Abstract: The Cigarette Purchase Task (CPT) is a behavioral economic method for assessing demand for cigarettes. Growing interest in behavioral correlates of tobacco use in clinical and general populations as well as empirical efforts to inform policy has seen an increase in published articles employing the CPT. Accordingly, an examination of the published methods and procedures for obtaining these behavioral economic metrics is timely. The purpose of this investigation was to provide a review of published approaches to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 76 publications
(28 citation statements)
references
References 99 publications
(147 reference statements)
3
25
0
Order By: Relevance
“…The present results further demonstrate the utility of the CPT for providing a detailed, quantitative characterization of the relative reinforcing value of smoking (i.e., smoking motivation) (Gonzalez-Roz et al, 2019;Reed et al, 2020;Zvorsky et al, 2019). Consistent with prior studies in adolescent (Bidwell et al, 2012) and adult smokers (Gonzalez-Roz et al, 2020;O'Connor et al, 2016), the five conventional CPT indices reduced to two latent factors.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present results further demonstrate the utility of the CPT for providing a detailed, quantitative characterization of the relative reinforcing value of smoking (i.e., smoking motivation) (Gonzalez-Roz et al, 2019;Reed et al, 2020;Zvorsky et al, 2019). Consistent with prior studies in adolescent (Bidwell et al, 2012) and adult smokers (Gonzalez-Roz et al, 2020;O'Connor et al, 2016), the five conventional CPT indices reduced to two latent factors.…”
Section: Discussionsupporting
confidence: 89%
“…The CPT task has participants estimate how many cigarettes they would smoke in a 24-hr period across escalating hypothetical prices (Jacobs & Bickel, 1999). Prior studies have shown that results are functionally congruent across versions where participants consume purchased cigarettes and the hypothetical version used in the present study where participants simply estimate consumption (Nighbor et al, 2020;Wilson et al, 2016). Participants were instructed to imagine making purchases in a context where they have (a) the same income/savings as they do currently, (b) no access to cigarettes or nicotine products other than those offered at these prices, (c) that they would smoke the cigarettes purchased over the next 24 hours, and (d) are unable to save or stockpile cigarettes.…”
Section: Behavioral Measuresmentioning
confidence: 84%
“…Just as there is variability in how demand is collected, there is variability in how demand is analyzed Reed et al, 2020) and demand is typically analyzed in one of two ways. The first approach is to fit a demand model to the overall group-level consumption.…”
Section: Mixed-effects Modelingmentioning
confidence: 99%
“…A hypothetical cigar purchase task (CPT) was administered to cigar users only. Purchase tasks are used to understand how an individual values a tobacco product, for example, Reed et al (2020) and have been validated across a number of studies for cigarette use (Grace et al, 2015; Mackillop et al, 2016; Wilson et al, 2016).…”
Section: Methodsmentioning
confidence: 99%